2002
DOI: 10.1029/2002tc902003
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic inversion in the Santa Barbara System of the central Andean foreland thrust belt, northwestern Argentina

Abstract: [1] The Santa Barbara System (SBS) of northern Argentina is a 400 km long segment of the Subandean foreland thrust belt. It is characterized by predominantly west verging, relatively high-angle thrust faults. Many of these faults are reactivated normal faults from one branch of a complex Cretaceous to Paleogene rift system. Heteroaxial folding in parts of the SBS is probably due to a slight component of range-parallel dextral strike-slip motion acting on preexisting faults striking north and NE during inversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
157
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(185 citation statements)
references
References 31 publications
10
157
0
1
Order By: Relevance
“…The tectonic inversion of former extensional faults played a key role in the configuration of the Santa Bárbara System, at the NE of the study area (Grier et al 1991;Coutand et al 2001;Kley et al 2005;Carrera et al 2006;Hongn et al 2007). The Eastern Cordillera involves the inversion of Cretaceous syn-rift faults, but also basement faults that were not active during the rifting stage (Bianucci et al 1981;Grier et al 1991;Cristallini et al 1997;Kley & Monaldi 2002).…”
Section: Geological Settingmentioning
confidence: 99%
“…The tectonic inversion of former extensional faults played a key role in the configuration of the Santa Bárbara System, at the NE of the study area (Grier et al 1991;Coutand et al 2001;Kley et al 2005;Carrera et al 2006;Hongn et al 2007). The Eastern Cordillera involves the inversion of Cretaceous syn-rift faults, but also basement faults that were not active during the rifting stage (Bianucci et al 1981;Grier et al 1991;Cristallini et al 1997;Kley & Monaldi 2002).…”
Section: Geological Settingmentioning
confidence: 99%
“…For example, mild to moderate inversion in intraplate basins has been observed in numerous North Atlantic basins (Cartwright, 1989;Chapman, 1989;Hayward & Graham, 1989;Roberts et al, 1993;Sinclair, 1995;Thomas & Coward, 1995) or in the North German Basin (Kossow et al, 2000;Kossow & Krawczyk, 2002;Gemmer et al, 2003). In addition, strongly shortened half grabens have been documented in the Alps (Gillcrist et al, 1987), with prominent examples found in the Central Andes (Kley & Monaldi, 2002) and Atlas mountains (Beauchamp et al, 1999;Teixell et al, 2003). Huyghe & Mugnier (1995) suggested that the nature of inversion in mildly inverted intraplate basins is di¡erent from inversion in orogenic belts where extensional structures are typically fully reversed, creating topography and exposure of former basin strata (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This low resolution image of deformation was complemented by a detailed analysis of shortening across the plateau at 21°S±1° by Oncken et al (2006). They used the available data on horizontal shortening (e.g., Kley and Monaldi, 2002;Echavarría et al, 2003;Elger et al, 2005) and recently published ages from synkinematic growth deposits and unconformities (e.g., Horton, 2005;Ege, 2004). They collected such data for all individual structures building each morphotectonic unit of the Southern Central Andes.…”
Section: Structural Developmentmentioning
confidence: 99%